Wound Healing and Wound Care in Neonates: Current Therapies and Novel Options. (June 2020) - Steen, Emily H.; Wang, Xinyi; Boochoon, Kieran S.; Ewing, Donald C.; Strang, Harrison E.; Kaul, Aditya; Masri, Leighanne; Balaji, Swathi; Hollier, Larry H.; Keswani, Sundeep
Abstract : GENERAL PURPOSE: To provide wound care information that considers the specific physiology of neonates. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will: 1. Differentiate the use of hydrocolloids, hydrogels, foam dressings, and barrier creams in the neonatal population. 2. Identify issues related to the use of solvents, alginates, collagen dressings, and negative-pressure wound therapy in neonates. ABSTRACT: OBJECTIVE To discuss what is known about the wound milieu in premature and full-term neonates, including the unique challenges pediatric clinicians face, the therapies that have proven effective, and the therapies contraindicated for use in neonatal wound healing to guide treatment that accounts for the specific physiological characteristics of this often overlooked population. DATA SOURCES: Data were collected on neonatal wound healing from a wide variety of sources, including PubMed, Google Scholar, journals, and textbooks. STUDY SELECTION: Selection criteria included publications focused on the differences and nuances of wound healing in neonates in comparison with all other age groups. DATA EXTRACTION: Data were extracted based on articles covering wound healing therapies with proven effectiveness in neonates. Terms for neonatal wound care were compiled, and then a comprehensive literature search was performed by the authors. DATA SYNTHESIS: Although many therapies are safe for treatment of older children and adolescents, most have not been explicitly tested for neonatal use. This article reviews therapies with proven effectiveness and/or specific concerns in the neonatal population. CONCLUSION: This review sheds light on the advantages and disadvantages of current standards of care regarding wound healing for neonates to direct researchers and clinicians toward developing treatments specifically for this delicate population.